Factors That Influence the Succes of Application of Technology in Learning: Teacher Work Motivation and Organizational Support - Johny Taroreh; Sjeddie Watung; Cecilia Lelly Kewo; Febriyani Maureen Lidya Rattu (Universitas Pendidikan Ganesha, 2023)
The problem with teachers in general is that they have not fully mastered the use of technology in learning. To evaluate the effect of teacher work motivation and organizational support on the application of technology is the goal to be achieved in this study. This study used a quantitative method, namely explanatory research. Samples were taken using simple random sampling technique of 115 respondents. Data collection was carried out through questionnaires and interviews. Test method with validity and reliability tests. Validity test to correlate questions with the total score of each variable. The data that has been collected is then analyzed using descriptive statistical analysis methods. The results of the study show that partially the teacher's work motivation has a positive and significant effect on the successful application of technology by 9.2%. Then the support of school organizations partially has a positive and significant effect on the successful application of technology by 36.7%. Simultaneously work motivation and organizational support affect the success of applying technology in learning by 59%. Compared to teacher motivation, school support in the form of infrastructure services, availability of computers, internet networks makes a greater contribution to improving the quality of learning.